A Fool’s Crusade. Exile and Memory in Viet Thanh Nguyen’s “War Years” - Traina, Giacomo (Oltreoceano - Rivista sulle migrazioni, 2024)
The aim of this essay is to reconstruct in detail the historical events underlying Viet Thanh Nguyen’s short story “War Years” from the collection The Refugees (2017) and his debut novel The Sympathizer (2015). “War Years” gives a fictionalized version of the Homeland Restoration movement (Y.T Nguyen 2018), a wide array of anticommunist fronts born out of the ashes of the South Vietnamese military in the wake of the 1975 defeat. These fronts were responsible for various unsuccessful attempts to infiltrate the motherland with the aim of overthrowing Hanoi’s rule during the eighties. Throughout the essay, the emphasis will be on the dual narrative strategy (realism vs. satire) via which the author fictionalizes the story of the Homeland Restoration movement across the two texts. While The Sympathizer reframes this little-known story as a quasi-surreal narrative, “War Years” investigates the impact of the Homeland Restoration movement on the daily life of Vietnamese refugees in Reagan-era San José thus giving agency to characters and actors who have been traditionally excluded from canonical Vietnam War narratives.